The use of herbal medicines by people with cancer: a qualitative study - Grieve Robert; Warmington Sally A; Damery Sarah L; Greenfield Sheila M; Wilson Sue; Gratus Christine; Steven Neil M; Routledge Philip (BMC, 2009)
Abstract Background Between 7% and 48% of cancer patients report taking herbal medicines after diagnosis. Because of the possibility of unwanted side effects or interactions with conventional treatments, people with cancer are generally advised to tell the professionals treating them if they are taking any form of medication, including herbal medicines and supplements. Studies suggest that only about half do so and that the professionals themselves have at best very limited knowledge and feel unable to give informed advice. This study is intended to inform the future development of information resources for cancer patients, survivors and healthcare professionals including tools for use before or during consultation to make it easier for patients to mention, and for healthcare professionals to ask about, use of herbal medications. Methods/design This is a three-phase study. In phase 1, a systematic review of the literature on self-medication with herbal medicines among UK populations living with cancer will establish the current evidence base on use of herbal medicine, sources of information, characteristics and motivations. This will allow us to better understand what aspects need further investigation and inform the topic guide for a qualitative study (phase 2). Six focus groups of six to eight cancer patients who have used at least one herbal preparation since diagnosis will explore behaviour, beliefs, knowledge, information sources and needs in an informal conversational setting. Informed by the findings of the systematic review and qualitative study, in phase 3 we will construct and pilot a questionnaire for a future large-scale survey to quantify and prioritise people's beliefs, needs and information preferences. Discussion Despite known interactions with conventional cancer treatments and contraindications for some herbal remedies with specific cancers, reliable information resources for patients are very limited. Identifying cancer patients' information needs and preferences is the first step in creating a suitable resource for both the public and the professionals advising them.